Exploring the Antecedents in Formation of Attitude Towards Indian Cellular Services - Virk, Nirmaljeet (Indian Journal of Marketing, 2014)
For consumers of a service organization, formation of attitude depends on the perception of services that a firm provides (having experienced the services themselves and by hearing the feedback about the services from their peer or reference group). Knowledge of such factors that influence customers' perception in service encounters, is, therefore, critical, particularly at a time when competition is huge and everybody is focusing to win over the customer by offering one thing or the other. As the telecom industry in India is growing at a rapid pace, the present study attempted to identify the major factors which lead to consumers' attitude formation towards these service providers. Primary data were collected from 267 respondents through a structured questionnaire. Factor analysis was used to extract the factors which lead to attitude formation towards Indian cellular service providers. Four factors namely, Service Quality, Physical Evidence, Price Perception, and Corporate Image were extracted from the collected data. The findings showed that for positive attitude building of customers towards services, a service provider must be conscious about the above-mentioned factors.